Application of Machine Learning and Data Mining (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The following special issue contains 14 articles accepted and published in the Special Issue "Mathematics and Computer Science, 2024" of the MDPI journal Mathematics. The included articles cover a wide range of topics related to the theory and applications of Machine Learning and Data Mining, as well as their extensions and generalizations. These topics include, but are not limited to, supervised, unsupervised, and self-learning methods; large-scale data mining; applicable neural networks and artificial intelligence; neural network-based industrial applications; neural models for natural language processing; deep learning for health informatics and biomedical engineering; graph convolutional neural networks and their applications; deep reinforcement learning and its applications; deep sparse and low-rank representation; and computer vision and pattern recognition techniques. In addition to these core areas, the authors of the included articles also delve into advanced methodologies and innovative approaches within these fields. The collection aims to provide comprehensive insights into recent advancements and emerging trends in Machine Learning and Data Mining, making it a valuable resource for researchers, practitioners, and students interested in the latest developments in these dynamic disciplines.